Optimising Human Resources Capacity: Driving Adoption of Latest Technology and Driving Business Innovation amidst the Dynamics of the Digital Era - Ryketeng, Masdar; Syachbrani, Warka; Syamsuri (ADMAN: Journal of Contemporary Administration and Management, 2023)
The rapid development of information and communication technology has significantly changed the business landscape, creating new challenges as well as opportunities for companies. In this digital era, companies are not only faced with increasingly fierce global competition but also have to face pressure to continuously adapt to the latest technological developments. Thus, this study aims to investigate the best strategies to optimise HR capacity to drive adoption of the latest technology and trigger business innovation. The method involved a thorough exploration of the literature using qualitative analysis, with a view to gaining a thorough understanding of the topic from 2012 to 2023. The study results show that in the face of the dynamics of the digital era, it is important for companies to continuously adapt and optimise their human resource (HR) capacity in order to meet the challenges of business transformation triggered by technological advancements. HR needs to not only be skilled in mastering technology, but also have high innovation capabilities. Innovation is not just an optional strategy, but an urgent need to maintain relevance and competitiveness in an ever-evolving market. The results show that training and development is key to improving HR capacity, especially through structured training programmes that focus on technology skills. The challenge of change resistance needs to be overcome through effective change management and full support from leadership in shaping a culture of innovation.